Donor–Acceptor (D–A)‐Substituted Polyyne Chromophores: Modulation of Their Optoelectronic Properties by Varying the Length of the Acetylene Spacer. Issue 38 (6th August 2013) - Štefko, Martin; Tzirakis, Manolis D.; Breiten, Benjamin; Ebert, Marc‐Olivier; Dumele, Oliver; Schweizer, W. Bernd; Gisselbrecht, Jean‐Paul; Boudon, Corinne; Beels, Marten T.; Biaggio, Ivan; Diederich, François
Abstract A series of donor–acceptor‐substituted alkynes, 2 a–f, was synthesized in which the length of the π‐conjugated polyyne spacer between the N, N‐diisopropylanilino donor and the 1, 1, 4, 4‐tetracyanobuta‐1, 3‐diene (TCBD) acceptor was systematically changed. The effect of this structural change on the optoelectronic properties of the molecules and, ultimately, their third‐order optical nonlinearity was comprehensively investigated. The branched N, N‐diisopropyl groups on the anilino donor moieties combined with the nonplanar geometry of 2 a–f imparted exceptionally high solubility to these chromophores. This important property allowed for performing INADEQUATE NMR measurements without 13C labeling, which, in turn, resulted in a complete assignment of the carbon skeleton in chromophores 2 a–f and the determination of the 13C–13C coupling constants. This body of data provided unprecedented insight into characteristic 13C chemical shift patterns in push–pull‐substituted polyynes. Electrochemical and UV/Vis spectroscopic studies showed that the HOMO–LUMO energy gap decreases with increasing length of the polyyne spacer, while this effect levels off for spacers with more than four acetylene units. The third‐order optical nonlinearity of this series of molecules was determined by measuring the rotational averages of the third‐order polarizabilities (γrot) by degenerate four‐wave mixing (DFWM). These latter studies revealed high third‐order optical nonlinearities for the new chromophores; most importantly, they provided fundamental insight into the effect of the conjugated spacer length in D–A polyynes, that can be exploited in the future design of suitable charge‐transfer chromophores for applications in optoelectronic devices.